2018
DOI: 10.1038/s41598-018-34611-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Calf-Hood Nutrition on the Transcriptional Regulation of the Hypothalamic-Pituitary-Testicular axis in Holstein-Friesian Bull Calves

Abstract: The aim of this study was to investigate the effect of early calf-hood nutrition on the transcriptomic profile of the arcuate nucleus of the hypothalamus, anterior pituitary and testes in Holstein-Friesian bulls. Holstein-Friesian bull calves with a mean (±S.D.) age and bodyweight of 19 (±8.2) days and 47.5 (±5.3) kg, respectively, were offered a high (n = 10) or low (n = 10) plane of nutrition in order to achieve an overall growth rate of 1.2 and 0.5 kg/day. At 126 (±3) days of age, calves were euthanized, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…The systemic concentrations of the various metabolites assessed in this study were within the normal range for calves in positive energy balance, were consistent with other recent studies ( Byrne et al, 2018 ; English et al 2018b ), and, in general, reflected the divergence in average metabolic status and nutrient intake generated by the two contrasting planes of nutrition employed. Glucose concentrations generally reflected the prevailing plane of nutrition, particularly the greater lactose and starch intake of the calves fed the HI diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The systemic concentrations of the various metabolites assessed in this study were within the normal range for calves in positive energy balance, were consistent with other recent studies ( Byrne et al, 2018 ; English et al 2018b ), and, in general, reflected the divergence in average metabolic status and nutrient intake generated by the two contrasting planes of nutrition employed. Glucose concentrations generally reflected the prevailing plane of nutrition, particularly the greater lactose and starch intake of the calves fed the HI diet.…”
Section: Discussionsupporting
confidence: 91%
“…While the positive impact of early-life nutrition on sexual development in the bull is clear, the optimum window of development to target, as well as the precise underlying molecular mechanisms involved, are yet to be fully elucidated ( Kenny et al, 2018 ). Our group has previously reported that a high-energy plane of nutrition (high-energy diet vs. low-energy diet) during the first 18 wk of life altered the physiological and molecular control of the hypothalamus (arcuate nucleus region), anterior pituitary, and testes in the bull calf ( English et al, 2018a ), consistent with advancing puberty by approximately 4 wk ( Byrne et al, 2017a ). While our previous molecular-based evaluations have provided insight into the impact of early-life plane of nutrition on HPT regulation, it is not clear whether these differences observed at 18 wk of age were a result of biochemical events that occurred earlier during the aforementioned prepubertal LH transient rise which typically occurs between 8 and 20 wk of age ( Rawlings and Evans, 1995 ; Evans et al, 1996 ) or prior to this time.…”
Section: Introductionmentioning
confidence: 93%
“…The hastened onset of puberty was accompanied by an increase in scrotal circumference and in testosterone concentration ( Byrne et al, 2018b ), indicating that HM bull testes matured earlier. In addition, at 4 months of age, calves subjected to a high plane of nutrition had greater seminiferous tubule diameter, more mature spermatogenic cells and more Sertoli cells, compared to calves on a low plane of nutrition ( English et al, 2018 ). In agreement with the increased testosterone concentration observed at a later age, calves in the high plane group also exhibited a tendency for greater peripheral LH concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, if we select the peripheral INSL3 concentration at 4 months, which represents the time within the prepubertal period when the INSL3 profile is increasing most rapidly and consequently shows most discriminatory ability, then this value (and unlike other parameters, except for IGF1) is highly predictive not only of the timing of puberty (Fig 7A), but also of later scrotal circumference, though not of later testis weight nor average sperm density (12–18 months). In an independent study, INSL3 mRNA in the testes of calves slaughtered at a comparable time-point (18 weeks) was also shown to be significantly reduced if the calves were fed a low plane of nutrition [46]. IGF1 is known to reflect growth potential (and hence is a logical readout of improved nutritional status) and is also an important co-factor in the expression of numerous gonadally expressed genes [47].…”
Section: Discussionmentioning
confidence: 99%